Q fever and coxiellosis in Brazil: an underestimated disease? A brief review - de Souza, Eline Almeida Rodrigues; André, Marcos Rogério [UNESP]; Labruna, Marcelo Bahia; Horta, Mauricio Claudio (FapUNIFESP (SciELO), 2022)
Q fever, caused by the γ-proteobacterium Coxiella burnetii, is a zoonosis of great importance and global impact. This agent has high transmissibility and can spread over long distances via wind, in which a small number of aerosolized particles are needed to infect susceptible hosts. The clinical diagnosis of Q fever is difficult owing to the variety of clinical signs shared with other diseases. In Brazil, studies related to C. burnetii are constantly being conducted, and this review aims to increase the number of approaches already studied, leading to the following question: is Q fever an unknown, neglected disease, or does it have a focal occurrence in certain areas (exotic/ rare) in the country?.
Febre Q e coxielose no Brasil: uma doença subestimada? Uma breve revisão
Keywords: Coxiella burnetii; humans; infectious; small ruminants; zoonosis